Sertifikasi Hijau dan Perilaku Konsumen: Tinjauan Sistematis Praktik Keberlanjutan Hotel, Tantangan, dan Wawasan - Sulistiyo, Tri Djoko; Oktaviani, Desy; Anggiani, Sarfilianty (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2025)
This systematic literature review aims to explore sustainability practices in the hotel industry, focusing on organizational factors, consumer behavior, and the role of environmental certifications. By analyzing nine peer-reviewed studies published between 2020 and 2025, the review identifies key sustainability practices, including energy efficiency, waste management, and water conservation. The findings emphasize the importance of strong management support, an organizational culture focused on sustainability, and effective employee training in driving the adoption of sustainable practices. Furthermore, environmental certifications such as LEED, Green Key, and EarthCheck were found to enhance consumer trust and influence hotel choice, though the effectiveness of these certifications depends on their clarity and credibility. The review also highlights the evolving role of consumer preferences, especially in the post-pandemic context, where health, safety, and comfort are prioritized alongside environmental sustainability. A proposed conceptual framework integrates these factors, offering a comprehensive model to understand the dynamics of sustainability in the hotel industry. The review concludes with practical and theoretical implications for hotel managers and suggestions for future research, including the need for longitudinal studies, cross-cultural research, and exploration of the role of digital technologies in sustainability efforts. Keywords: sponge cake, marketing strategy, social media, aron flour and Bogor beans flour